2021
DOI: 10.46909/journalalse-2021-018
|View full text |Cite
|
Sign up to set email alerts
|

Plant Spacing and Its Effect on Yield, Fibre Quality and Physiological Parameters in Cotton

Abstract: The purpose of this study was to see how changing plant spacings affected cotton yield, yield components, fibre quality traits, and physiological parameters. In this study, six plant spacings (no thinning, 5, 10, 15, 20, and 25 cm) were investigated. Plant density caused significant differences in the number of first fruiting branches, number of bolls, ginning percentage, seed cotton yield, fibre yield, and normalised difference vegetative index (NDVI). Plant height, the number of sympodial branches, number of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 37 publications
0
2
0
Order By: Relevance
“…Our results suggest that as the yields of 701 and 1432 did not differ significantly in D1 and D2, lower densities could be preferable as they reduce the production cost (Khan et al, 2017). In their study, Altundag and Karademir (2021) have also concluded that plant density does not nessecerily affect the yield components of cotton.…”
Section: Discussion Discussion Discussionmentioning
confidence: 93%
“…Our results suggest that as the yields of 701 and 1432 did not differ significantly in D1 and D2, lower densities could be preferable as they reduce the production cost (Khan et al, 2017). In their study, Altundag and Karademir (2021) have also concluded that plant density does not nessecerily affect the yield components of cotton.…”
Section: Discussion Discussion Discussionmentioning
confidence: 93%
“…Ali et al (2021) indicated that fiber strength and length uniformity index were not significantly influenced by plant distribution systems. Altundag and Karademir (2021) found that the differences among planting spacings (5, 10, 15, 20 and 25 cm) were not statistically significant for fibre micronaire, fibre length (mm), fibre strength and fibre uniformity (%).…”
Section: Vi1 Effect Of Hill Spacingmentioning
confidence: 86%